Search for long-lived particles using nonprompt jets and missing transverse momentum with proton-proton collisions at √s=13TeV; Physics Letters B; Vol. 797 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen